Supramolecular Optimization of Sensory Function of a Hemicurcuminoid through Its Incorporation into Phospholipid and Polymeric Polydiacetylenic Vesicles: Experimental and Computational Insight - Akhmadeev, Bulat S.; Retyunskaya, Olga O.; Podyachev, Sergey N.; Katsyuba, Sergey A.; Gubaidullin, Aidar T.; Sudakova, Svetlana N.; Syakaev, Victor V.; Babaev, Vasily M.; Sinyashin, Oleg G.; Mustafina, Asiya R. (Polymers, 2023)
This work presents the synthesis of a new representative of hemicurcuminoids with a nonyloxy substituent (HCur) as a fluorescent amphiphilic structural element of vesicular aggregates based on phosphatidylcholine (PC), phosphatidylserine (PS), and 10,12-pentacosadiynoic acid (PCDA). Both X-ray diffraction analysis of the single crystal and 1H NMR spectra of HCur in organic solvents indicate the predominance of the enol-tautomer of HCur. DFT calculations show the predominance of the enol tautomer HCur in supramolecular assemblies with PC, PS, and PCDA molecules. The results of the molecular modeling show that HCur molecules are surrounded by PC and PS with a rather weak exposure to water molecules, while an exposure of HCur molecules to water is enhanced under its supramolecular assembly with PCDA molecules. This is in good agreement with the higher loading of HCur into PC(PS) vesicles compared to PCDA vesicles converted into polydiacetylene (PDA) ones by photopolymerization. HCur molecules incorporated into HCur-PDA vesicles exhibit greater planarity distortion and hydration effect in comparison with HCur-PC(PS) ones. HCur-PDA is presented as a dual fluorescence-chromatic nanosensor responsive to a change in pH within 7.5–9.5, heavy metal ions and polylysine, and the concentration-dependent fluorescent response is more sensitive than the chromatic one. Thus, the fluorescent response of HCur-PDA allows for the distinguishing between Cd2+ and Pb2+ ions in the concentration range 0–0.01 mM, while the chromatic response allows for the selective sensing of Pb2+ over Cd2+ ions at their concentrations above 0.03 mM.